2019
DOI: 10.1097/prs.0000000000006166
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Transformation with Facial Feminization Surgery: Improved Anatomical Accuracy with Virtual Planning

Abstract: Background: Facial feminization surgery entails a series of surgical procedures that help the transwoman pass as their affirmed gender. Although virtual surgical planning, with intraoperative cutting guides, and custom plates have been shown to be helpful for craniomaxillofacial reconstruction, they have not yet been studied for facial feminization surgery. The authors used cadaveric analysis for morphologic typing and to demonstrate the utility of virtual surgical planning in facial feminization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…The use of VSP and 3DP provides a significant assistance during the execution of the planned FFS in a safe (avoiding nerve injury, intracranial entry, and other complications), accurate (precise and desired intervention), and efficient (reduced operative time) way. 20 25 26 In this regard, patient-specific, colored bony thickness measurement maps allow for safer execution of the plan and more precise surgical intervention (e.g., burring or osteotomy of the frontal bone during feminizing foreheadplasty) 25 ( Fig. 1 ).…”
Section: Objectives Of Implementing Vsp and 3dp To Ffsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of VSP and 3DP provides a significant assistance during the execution of the planned FFS in a safe (avoiding nerve injury, intracranial entry, and other complications), accurate (precise and desired intervention), and efficient (reduced operative time) way. 20 25 26 In this regard, patient-specific, colored bony thickness measurement maps allow for safer execution of the plan and more precise surgical intervention (e.g., burring or osteotomy of the frontal bone during feminizing foreheadplasty) 25 ( Fig. 1 ).…”
Section: Objectives Of Implementing Vsp and 3dp To Ffsmentioning
confidence: 99%
“…3 12 13 14 15 16 17 18 19 20 In addition to multiple studies describing the utilization of VSP and 3DP in head and neck reconstruction, cranial vault reconstruction, craniomaxillofacial trauma, and aesthetic surgery, 16 18 21 22 23 24 lots of studies involving the use of VSP and 3DP in FFS have also been published recently. 17 19 20 25 26 27 In this review, we will discuss the current applications of VSP and 3DP in FFSs along with reported outcomes in the literature.…”
mentioning
confidence: 99%
“…There is likely benefit to preoperative planning and using cutting guides for trainees, but it is not clear that there is the same benefit for proficient surgeons. In the Gray et al [23] study, the rate of success without VSP was only 79%, meaning that in these cadavers 21% of the time there was intracranial or dural injury. Previous reports mentioned in this paper show a far lesser complication rate, and 0% intracranial entry, indicating that this is a safe procedure in experienced hands.…”
Section: Virtual Surgical Planningmentioning
confidence: 99%
“…Given the complexity of bony osteotomies necessary to achieve a gender-congruent facial appearance, virtual surgical planning is often indicated. 35…”
Section: Cpt Codingmentioning
confidence: 99%